2014
DOI: 10.1089/cyber.2013.0658
|View full text |Cite
|
Sign up to set email alerts
|

Being Bad in a Video Game Can Make Us Morally Sensitive

Abstract: Several researchers have demonstrated that the virtual behaviors committed in a video game can elicit feelings of guilt. Researchers have proposed that such guilt could have prosocial consequences. However, this proposition has not been supported with empirical evidence. The current study examined this issue in a 2 · 2 (video game play vs. real world recollection · guilt vs. control) experiment. Participants were first randomly assigned to either play a video game or complete a memory recall task. Next, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 17 publications
3
54
0
1
Order By: Relevance
“…They might, for example, encourage viewers to engage in the kind of effortful sociomoral reasoning that Bartsch and Oliver (2011) suggest is related to meaningful entertainment experiences. For example, research has shown that video game decisions can result in guilt reactions in players (Grizzard et al 2014). More specifically, players felt more guilt when committing acts of violence in a video game when the violence was unjustified than when it was not ).…”
Section: Meaningfulness and Video Gamesmentioning
confidence: 99%
“…They might, for example, encourage viewers to engage in the kind of effortful sociomoral reasoning that Bartsch and Oliver (2011) suggest is related to meaningful entertainment experiences. For example, research has shown that video game decisions can result in guilt reactions in players (Grizzard et al 2014). More specifically, players felt more guilt when committing acts of violence in a video game when the violence was unjustified than when it was not ).…”
Section: Meaningfulness and Video Gamesmentioning
confidence: 99%
“…The model also suggests, however, that the salience of moral foundations can be altered by media exposure. In line with this suggestion, the most recent research concerning video games and MFT found that violating the care/harm and fairness/cheating domains (via unjustified video game violence) increased the salience of these domains, and this effect was mediated by guilt (Grizzard et al, 2014).…”
Section: Chapter 2 Literature Review Video Games and Moral Foundationsmentioning
confidence: 72%
“…Obtaining a measure outside of the lab context was preferable because previous research has suggested that the salience of moral foundations may temporarily change after in-game moral violations (Grizzard et al, 2014).…”
Section: Moral Foundations Saliencementioning
confidence: 99%
See 2 more Smart Citations